2017
DOI: 10.1038/ng.3807
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric subgenome selection and cis-regulatory divergence during cotton domestication

Abstract: Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
318
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 366 publications
(369 citation statements)
references
References 84 publications
23
318
5
2
Order By: Relevance
“…Most prior genetic diversity studies have suggested that no obvious genetic structure exists in Chinese upland cotton populations (Fang et al ; Sun et al ; Wang et al ). In our study, we present strong evidence that CUCSG has highly divergent genomic signatures for the different lineages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most prior genetic diversity studies have suggested that no obvious genetic structure exists in Chinese upland cotton populations (Fang et al ; Sun et al ; Wang et al ). In our study, we present strong evidence that CUCSG has highly divergent genomic signatures for the different lineages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of markers and genome coverage was limited, leading to uncertainty about the population structure and, thus, hampering the identification of favorable alleles. Recent single‐nucleotide polymorphism (SNP)‐based studies were also unable to clearly illuminate the population structure of upland cotton (Fang et al ; Sun et al ; Wang et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Domestication of cotton is predicted to take place approximately 5000 years ago [117]; two allotetraploid species, G. hirsutum L. and G. barbadense L. were independently domesticated into Upland or American and Pima or Egyptian cotton, respectively, for their higher fiber yield and wider geographical distribution [119]. The domestication characteristics were accompanied by many morphological changes including loss of photoperiod sensitivity, reduction in seed dormancy, and conversion from tree-like wild species to an annual crop [119,120•]. …”
Section: Epigenetics Regulation In Polyploid Evolution and Domesticationmentioning
confidence: 99%
“…In addition, re‐sequencing the genome for which there is a reference genome available permits exploration of the association between sequence variations. Recent comprehensive genome assessment by genome‐wide re‐sequencing of 34 (Page et al ., ), 318 (Fang et al ., ), 147 (Fang et al ., ) and 352 (Wang et al ., ) cotton accessions represented extensive collections in order to identify genome regions that are signature of selection. These studies provide new genomic resources that significantly advance molecular breeding in cotton.…”
Section: Cotton Genome Sequencing: Progress and Implicationsmentioning
confidence: 99%